Egy korai francia szál David Ricardo adóelméletéhez - Csató Katalin (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
– Interpretations of David Ricardo's (and Adam Smith's) tax theory are presently dominated by an Anglo-Saxon perspective, though French physiocrats also played a role in its formation. Recent studies on economic thought often include a look at the historical precedents of a theory. This has given the impetus to the author of this study to review the historical antecedents of a tax theory. Smith and Ricardo's school dealt with labour theory, the relation of tax burden and income types influencing economic behaviour among others. Their predecessors were the French physiocrats from whom Smith and Ricardo adopted the principle of a single tax, a tax levied directly on landowners' rents.. This is an income' which is generated but does not produce wealth and can therefore be used for public purposes. Their tax-incidence analysis followed a physiocratic logic. The present paper , in addition to outlining the basic principles of the physiocratic taxation, discusses the reform plans of some of the major physiocrats.
Keywords: P16; P43; 330; Adam Smith; David Ricardo; physiocrats; Quesnay; Turgot; Mercier de la Rivière; Nicolas Baudeau; tax theory; rent; tax-incidence